Venous Thrombo-Embolism in Hospitalized SARS-CoV-2 Patients Treated with Three Different Anticoagulation Protocols: Prospective Observational Study - Longhitano, Yaroslava (Biology (Basel), 2020)
SIMPLE SUMMARY: The aims of this study are: (1) to analyze the risk of vein thrombosis and pulmonary embolism in patients affected by pneumonia due to Covid-19; (2) to evaluate conditions that could increase this risk; (3) to verify the efficacy of different doses of antithrombotic drugs to prevent these life-threatening complications. Seventy-four patients were enrolled (44 men and 30 women, average age 68.6). All of them were screened with lower limb ultrasound. Laboratory analyses including D-dimers were tested the same day. In case of clinical suspicion of pulmonary embolism, they performed a CT pulmonary angiography. A total of 28.4% (21 patients) were diagnosed with deep vein thrombosis or pulmonary embolism. This finding confirms that these patients were at increased risk of venous thromboembolism, as already reported from other studies. Mechanical ventilation, higher d-dimer levels, longer length of hospitalization and admission to intensive care unit showed to be statistically associated with thromboembolic events. In addition, the study showed that an intermediate or high dose of anticoagulation did not decrease the risk of thromboembolic events compared to lower doses. On the other hand, six patients reported severe bleeding that could be caused by higher doses of anticoagulant drugs. ABSTRACT: The purpose of this study is to assess thrombotic risk in CoViD-19/pneumonia patients with acute respiratory failure and to compare populations treated with three different antithrombotic prophylaxis protocols. The primary outcome is to analyze the prevalence of thrombotic events in hospitalized patients, while the secondary outcome is to analyze the correlation between different anticoagulation targets with thrombotic events. All patients referred to our hospital for acute respiratory failure due to COVID-19 pneumonia between 18 and 31 May 2020 were included. Seventy-four patients were enrolled (44 men and 30 women, average age 68.6). Diagnosis of venous thromboembolism was made in 21 cases (28.4%) and thrombotic events were associated with positive pressure ventilation support (p = 0.024) and hospitalization in ICU (p < 0.0001). These patients presented higher levels of D-dimer (p < 0.0001) and their hospital length of stay was >16 days longer. Forty-seven out of 74 patients (63.5%) received intermediate or therapeutic dose of anticoagulation, while twenty-seven patients (34.5%) received standard antithrombotic prophylaxis. The analysis showed that an intermediate or therapeutic dose of anticoagulation did not decrease the prevalence of thrombotic events. On the other hand, six patients reported severe hemorrhagic complications. Despite intermediate or therapeutic-dose of anticoagulation, a high number of patients with acute respiratory failure secondary to COVID-19 developed thrombotic complications.